Lifetime stress cumulatively programs brain transcriptome and impedes stroke recovery: benefit of sensory stimulation. - Fabíola C R Zucchi (Public Library of Science (PLoS), 2014)
Prenatal stress (PS) represents a critical variable affecting lifetime health trajectories, metabolic and vascular functions. Beneficial experiences may attenuate the effects of PS and its programming of health outcomes in later life. Here we investigated in a rat model (1) if PS modulates recovery following cortical ischemia in adulthood; (2) if a second hit by adult stress (AS) exaggerates stress responses and ischemic damage; and (3) if tactile stimulation (TS) attenuates the cumulative effects of PS and AS. Prenatally stressed and non-stressed adult male rats underwent focal ischemic motor cortex lesion and were tested in skilled reaching and skilled walking tasks. Two groups of rats experienced recurrent restraint stress in adulthood and one of these groups also underwent daily TS therapy. Animals that experienced both PS and AS displayed the most severe motor disabilities after lesion. By contrast, TS promoted recovery from ischemic lesion and reduced hypothalamic-pituitary-adrenal axis activity. The data also showed that cumulative effects of adverse and beneficial lifespan experiences interact with disease outcomes and brain plasticity through the modulation of gene expression. Microarray analysis of the lesion motor cortex revealed that cumulative PS and AS interact with genes related to growth factors and transcription factors, which were not affected by PS or lesion alone. TS in PS+AS animals reverted these changes, suggesting a critical role for these factors in activity-dependent motor cortical reorganization after ischemic lesion. These findings suggest that beneficial experience later in life can moderate adverse consequences of early programming to improve cerebrovascular health.